Fundamentals of solar astronomy - Bhatnagar Arvind; Livingston William (World Scientific, 2005)
There are several textbooks available on solar astronomy which deal with advanced astrophysical aspects of solar physics, and books which provide very elementary knowledge about the Sun. This book will help to bridge the gap. It aims to stimulate interest in solar astronomy, presenting at one place the basic methods and techniques used in the field, together with the latest findings and the excitement in solar physics. As solar astronomy is becoming very popular among amateur astronomers and laymen, the book provides the practical knowledge to build simple solar telescopes and other equipment for making solar observations. Amateur astronomers have made important contributions to solar astronomy, and this book will help to guide them in their endeavours. The book can also serve as a text for undergraduate and graduate students starting out on solar physics. Using it, graduate students can
Keywords: Astronomy; Sun